Metas parentais de socialização de mães e pais em relação ao desenvolvimento de seus filhos - Lins, Zoraide Margaret Bezerra (2011)
The main objective of this thesis was to examine parental socialization goals made by mothers and fathers with respect to the development of their children. The parental socialization goals were focused from integracionalist theories that view the development of children from the socio-cultural, placing the social dimension as a key aspect for human development. The parental socialization goals appear as a relevant field of research for understanding human development, because they are directly linked to parenting styles towards children, and socializing the fundamental axis around in which family interactions are articulated. The principle of bidirectionality demonstrates that development is a product of interaction between child characteristics and the characteristics of people who socialize, placing a sync between children s development and their parental behavior. The study used the technique of field research of a descriptive nature; the locus of the research was the participants' home residences in the city of Joao Pessoa, Paraiba. We interviewed 18 couples, each spouse individually with children 12 to 48 months, who responded to a questionnaire and an interview with semi-structure. The contents of the interviews were treated according to the technique of content analysis proposed by Bardin. Each interview was treated in depth and the results were analyzed in a quantitative and qualitative approach, presented in simple frequency of the reference values of verbal expressions, carried out by inference and interpretation, which allowed the identification of nine categories, 40 subcategories and 643 units of analysis. The results showed more similarities than differences between the goals pursued by mothers and fathers, verifying that the efforts are more likely to be that of combining responsibilities in pursuit of a co-parenting. The differences between mother and father were seen as complementary. The father is presented only as a reflection or replacement of the mother, but as a relevant participant to the child s development. Both mothers and fathers were more focused and committed to the responsibility of educating and caring for children observing a social construction of the current historical context.